IMPLEMENTASI KURIKULUM MERDEKA DALAM MENJAGA MUTU PEMBELAJARAN DI SDIT SAID NA’UM JAKARTA - Lubis, Sari Sartika; Sarnoto, Ahmad Zain; Tanrere, Syamsul Bahri (PMPP Lembaga Penelitian dan Studi Kebijakan, 2024)
The conclusion of this research is that The implementation of the independent curriculum at SDIT Said Na'um Jakarta is actually at a good stage in its implementation, but it is not yet fully in accordance with the concept of the actual independent curriculum. SDIT Said Na'um is still adapting in implementing this independent curriculum so that the results of the students' understanding at SDIT Said Na'um Jakarta has decreased slightly due to the lack of professional teachers in applying or applying this independent learning curriculum in teaching and learning activities in the classroom. However, with the evaluation of last year's learning, SDIT Said Na'um Jakarta teachers and the school principal and deputy head of curriculum will always try to improve the professionalism of the educators